Live Forensics Analysis Of Malware Identified Email Crimes To Increase Evidence Of Cyber Crime - Prawira, Yudhi Prawira; Samsudin, Samsudin (Digital Zone: Jurnal Teknologi Informasi dan Komunikasi, 2022)
Now days Email is the most important aplplication on the internet, this make email one of the industry’s most targeted sector for commiting cyber crimes. Email phishing and spam not only harm many parties but also consumes a lot of network bandwidth. Most spam are emotet malware. Trojan malware that targets internet users financial system to steal financial information and personal data by sending phishing. In this research, digital forensics analysis email crimes identified malware using live forensics and tools analyze digital evidence of email content, as wall as offVise, Wireshark, and Procmon to analyze malware activities. The results of the investigation of the email content carried out using software found digital evidence that could be used as a reference that attachment downloaded by the victim was Emoted type malware, when the victim opened it, this malware will be installed automatically on the victim’s computer. .